Sugar-Sweeten Beverage Consumption Is Associated With More Obesity and Higher Serum Uric Acid in Chinese Male Gout Patients With Early Onset - Li, Qian-Hua; Zou, Yao-Wei; Lian, Shu-Yan; Liang, Jin-Jian; Bi, Yu-Fei; Deng, Chao; Mo, Ying-Qian; Yang, Kui-Min; Dai, Lie (Frontiers in Nutrition, 2022)
Background: Early-onset gout has received increasing interest from researchers. Previous studies have reported that serum urate levels and prevalence of obesity are higher in early-onset gout patients than in later-onset gout patients. We explored the dietary habits of early-onset and later-onset gout patients and their association with clinical features. Methods: Gout patients completed a 10-item food frequency questionnaire. Early-onset gout patients were defined as gout onset before the age of 40, and onset after age 40 was classified as later-onset. Associations between dietary factors, obesity, and serum urate level of ≥600 μmol/L were assessed using logistic regression. Results: Among the 655 gout patients, 94.6% were males, and 59.1% presented with early-onset gout. All early-onset patients were males. Serum urate level was significantly higher in the early-onset group than in the later-onset group (550.7 vs. 513.4 μmol/L). The proportion of patients with a serum urate level of ≥600 μmol/L (40.3% vs. 26.2%) and obesity (27.6% vs. 10.7%) was higher in the early-onset group than in the later-onset group (all p<0.05). The early-onset group consumed more red meat (101–200 g/d: 43.6% vs. 26.0%), sugar-sweetened beverages (>4 times/week: 27.9% vs. 7.7%), and milk and milk products (1–2 times/week: 28.5% vs. 16.6%), but less alcohol (>84 g/d: 8.5% vs. 21.5%) and tea (>4 times/week: 35.7% vs. 52.4%; all p<0.05). Sugar-sweetened beverage intake was positively correlated with serum urate level of ≥600 μmol/L (compared with 4 times/week: adjusted odds ratio = 2.2, 95% confidence interval: 1.4, 3.7) and obesity (compared with < once/week [reference], >4 times/week: adjusted odds ratio = 2.2, 95% confidence interval: 1.2, 3.7). These correlations remained significant for early-onset gout patients. Conclusion: Sugar-sweetened beverage intake replaced alcohol as the main dietary risk factor for gout in early-onset patients, and this change was associated with a greater prevalence of obesity and higher serum urate level. Clinicians should provide specific dietary education for different generations of gout patients. The epidemic of sugar-sweetened beverage consumption should be considered for the development of public health policies for the prevention of gout.